BLIND SPOTS IN MUSEUM ANTHROPOLOGY: Ancient Egypt in the Ethnographic Museum. (30th July 2022) - Stevenson, Alice; Williams, Alice
Abstract : In the past few decades, the literature in museum anthropology has advocated efforts to be more transparent about its colonial origins, address the historical injustices of imperial collecting, and rethink display narratives in collaboration with source communities. In this paper, however, we question the extent to which the epistemic and political predicaments underlying ethnographic representations are being fundamentally and systematically confronted. As we highlight with the example of ancient Egyptian material, it is apparent that significant parts of museum holdings remain freighted by unquestioned colonial and Eurocentric discourses. We employ a case study of the Egyptian material redisplayed in the "World Cultures" gallery of the Horniman Museum, London, to demonstrate how the ethnographic museum continues to unwittingly produce "silences" around collections. To redress the lacunae we provide examples of the way in which this body of material could be more meaningfully integrated within museological discourses that have informed the rethinking of other aspects of world culture.